Local Flora and Fauna Conservation - A Role for Zoos, Aquariums and Botanical Gardens - Bechert, Ursula; Colodner, Debra C. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue highlights how zoos, aquariums, and botanical gardens have partnered with organizations and agencies to address local and regional conservation issues through research and education projects, rehabilitation programs, policymaking efforts, and other types of activities. Understanding how such partnerships are developed and maintained, the challenges encountered, and success stories (as well as unsuccessful ones) were of interest. Hopefully, the stories shared and lessons learned will guide other organizations in their local and regional conservation efforts.